IMPLEMENTASI KEBIJAKAN PERATURAN BUPATI MEMBERAMO RAYA NO. 8 TAHUN 2017 TENTANG TIM PENILAI KINERJA DALAM PROMOSI JABATAN PADA PEMERINTAH KABUPATEN MAMBERAMO RAYA - Moh. Sabrin Cono; Agustinus Fatem (JURNAL KEBIJAKAN PUBLIK, 2021)
This study aims to describe and analyze the implementation of Regent Regulation No. 8/2017 on the Performance Appraisal Team for Job Promotion in Mamberamo Raya Regency. and to analyze the supporting and inhibiting factors that influence it. The research method used is descriptive - qualitative by conducting direct observation, in-depth interviews, and documentation study. The data analysis process includes data collection, data reduction, data presentation, and drawing conclusions. The results showed that the implementation of the Mamberamo Raya Regent Regulation No. 08 of 2017 concerning the Performance Appraisal Team in Promotion of Position in the Mamberamo Raya Regency government has been going well. From the aspect of communication and information dissemination, coordination between institutions has been carried out. In the aspect of resources, it has sufficient quality and quantity to meet existing needs. Then the office facility environment is adequate to support performance. The disposition runs quite well based on the SOP and planning for allocating special budgets and the Bureaucratic Structure of the division based on the SOP and the authority and responsibility given according to the main tasks and functions of each field. Then, the supporting factor is that there are so many ASNs that meet the criteria for promotion. While the inhibiting factor is the problem of delay or lack of dissemination of information regarding selection for promotion to ASN, so that many ASN do not know about it.